Modification of Insulating Properties of Surfaces of Dielectric High-Voltage Devices Using Plasma - Pernica, Roman; Klíma, Miloš; Londák, Pavel; Fiala, Pavel (MDPI, 2024)
Plasma discharges under atmospheric pressure are applicable for modifying the electrical properties of dielectric surfaces. The aim of the plasma discharge treatment of such surfaces is to design a procedure so that its characteristic parameters improve the resulting levels of the breakdown electrical strength Eb when tested under pulsed or alternating electrical voltages. In this research, a set of functional experiments performed by using plasma in samples of two types of materials (thermoset, thermoplastic) were processed and evaluated, and the resulting effect of the magnitude of the breakdown electrical voltage, electrical intensity, and electrical conductivity of the surface were compared. A slit plasma chamber, previously described and parameterized, was employed to treat the surface of the dielectric samples. The surface structure was modified via plasma discharge without precursors, and methodologies were developed to evaluate these modifications with respect to the change in the electrical strength parameters of the insulator surface. Subsequently, the surface strength of the affected and unaffected samples was measured and evaluated as a function of exposure time, and the stability of the modification was assessed. The first methodical test showed that plasma discharge without precursors improved the long-term surface electrical strength of the dielectric surface. The test and its parameters were carried out with respect to feasibility in an industrial environment.

Plasma discharges under atmospheric pressure are applicable for modifying the electrical properties of dielectric surfaces. The aim of the plasma discharge treatment of such surfaces is to design a procedure so that its characteristic parameters improve the resulting levels of the breakdown electrical strength Eb when tested under pulsed or alternating electrical voltages. In this research, a set of functional experiments performed by using plasma in samples of two types of materials (thermoset, thermoplastic) were processed and evaluated, and the resulting effect of the magnitude of the breakdown electrical voltage, electrical intensity, and electrical conductivity of the surface were compared. A slit plasma chamber, previously described and parameterized, was employed to treat the surface of the dielectric samples. The surface structure was modified via plasma discharge without precursors, and methodologies were developed to evaluate these modifications with respect to the change in the electrical strength parameters of the insulator surface. Subsequently, the surface strength of the affected and unaffected samples was measured and evaluated as a function of exposure time, and the stability of the modification was assessed. The first methodical test showed that plasma discharge without precursors improved the long-term surface electrical strength of the dielectric surface. The test and its parameters were carried out with respect to feasibility in an industrial environment.
Modification of Insulating Properties of Surfaces of Dielectric High-Voltage Devices Using Plasma
Keywords: plasma; treatment; dielectric; electrical strength; numerical model; precursor; nanosurface; HV apparatus; plasma; treatment; dielectric; electrical strength; numerical model; precursor; nanosurface; HV apparatus